Forensic Linguistic Study and Sentence Analysis: Defamation by Artist Nikita Mirzani through Instagram Instastory - Lestari, Marzuanti Indah; Suryaman, Maman (BIRCU, 2023)
This article examines posts on the Instagram story status of artist NM whose sentences allegedly contain elements of defamation. The method used in this research is qualitative, namely describing data to determine elements that could tarnish someone's good name. Determining these elements requires forensic linguistic analysis, namely using linguistic evidence in law enforcement efforts. This evidence can be analyzed using lexical semantic analysis, grammatical semantics, pragmatic and sociopragmatic analysis, language style, as well as critical discourse analysis using Theo van Leeuween's theory which is part of forensic linguistic studies. Based on the analysis carried out, it was concluded that from a lexical semantics point of view, the words used in the uploaded sentences have a negative denotational meaning. Based on grammatical semantic analysis, this sentence means demeaning someone. Pramatically and sociopragmatically, the NM sentence contains 4 types of speech, namely representative, directive, expressive, and declaration based on the crime committed by DM. The language style used by NM uses sarcasm. Based on critical discourse analysis with Theo van Leeuween's theory, it uses inclusion with the discourse strategies of differentiation-indifferentiation, objectivation-abstraction, nomination-identification, and determination-indetermination.